Waterfront Development Strategy of The Old Kalimas Port Based on The Zoning of Tanjung Perak Port - Rabbani Kharismawan; Adi Nugroho Ngestitomo (Center for Scientific Publication, 2020)
Waterfront area is a special place in major cities around the world. Place to work, play or fulfilling a sense of curiosity. The old Kalimas Port is also no exception. As well as waterfront areas in other major cities, as a place for change (transition), with so many maritime facilities and a few new activities to attract people to the waterfront. When future generations are look back on this transition as historical moment of Kalimas River, they who are live today would feel that too many waterfront areas are separated from the public for a long time. The challenge of the waterfront development area is not only to help change the Kalimas riverfront as far as 2.5 km, to be a place to reflect modern traditions and a sense of place, but also take into account the history as an important role. By using a qualitative and descriptive method, the study aims to make a comparative analysis from some of the successful waterfront development concepts with the same character of the region, the old industrial riverfront area. The results are the waterfront development strategy, particularly in the Old Kalimas Port which is also part of the Tanjung Perak Port in Surabaya. It requires some special criteria, the vision and missions of the waterfront planning and development concepts. While in the old Port development strategy, in terms of the physical condition of the area and the Port authority policies, formulate zoning strategies as a macro strategy in the future sustainability of the region. The zoning strategy develop three micro zones; the old Port zone, recreational zone and commercial zone. The three zones have their own strategies which will be mutually support the sustainability of economic, social and cultural sector.